Encephalitozoonosis (nosematosis) causing bilateral cataract in a rabbit. Issue 9 (September 1976) - Ashton, N; Cook, C; Clegg, F
Abstract : Bilateral cataract due to a microsporidan believed to be Encephalitozoon cuniculi (also called Nosema cuniculi) is described as an incidental finding in a laboratory rabbit. The route of infection and the significance of the findings are discussed. This is apparently the first report of cataract due to this cause.